Relationship between increased anxiety during the COVID-19 pandemic and the presence of orofacial and cephalic pain of non-dental origin in students at the School of Health Sciences of the Amazonas State University (Research, Society and Development, 2022)
Patients with masticatory myofascial pain report greater neck deficiency, which in turn is correlated with regional muscle sensitivity. Sensitivity is attributed to a cascade of reactions that takeplace in the body and that lead to a greater perception of pain by the individual, influenced by the emotional state of the same. Stress situations generate changes in the balance of the hypothalamic-pituitary-adrenal (HPA) axis and this directly affects the muscle response of the trigger points present in Temporomandibular Disordersof muscular origin. Considering the current world situation, marked by important crises in public health and, more recently, the pandemic caused by the SARS-CoV-2 virus, to discuss the influence of emotional state on TMD, we propose a survey of the levels of anxiety present among students at the Higher School of Health Sciences of the Universidade do Estado do Amazonas.